BOLSONARISM AND POPULAR PROTECTION OF HUMAN RIGHTS DEFENDERS IN THE LEGAL AMAZON - Silva, Marcelo Fontenelle (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2023)
This essay brings reflections on the relationship between Bolsonarism and the popular protection of human rights defenders in the 9 states of the Legal Amazon. It begins with a reflection on the context of political polarization that we are experiencing, highlighting how the political platform of Bolsonarism leads to a regressive agenda on the issue of human rights. Next, a set of data extracted from the Laboratório de Estudos Geopolíticos da Amazônia Legal (LEGAL) on the last elections is analyzed, highlighting that the victory of a leftist president did not mean the defeat of Bolsonarism. Finally, we bring some considerations about the popular protection of human rights defenders, highlighting the importance of working in a network.